2019
DOI: 10.1002/jcsm.12446
|View full text |Cite
|
Sign up to set email alerts
|

The clinical relevance of adiposity when assessing muscle health in men treated with androgen deprivation for prostate cancer

Abstract: BackgroundAndrogen deprivation therapy (ADT) for prostate cancer (PCa) may prospectively decrease absolute lean mass (LM) and increase absolute fat mass (FM). Given that estimates of LM by dual‐energy X‐ray absorptiometry may be overestimated in obese people, this study examined the influence of adiposity on muscle health in men treated with ADT for PCa.MethodsThis cross‐sectional study examined the influence of adiposity on total and appendicular LM (ALM), muscle cross‐sectional (CSA), and muscle strength in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…This cross-sectional study was conducted parallel to baseline of a randomised controlled trial [27][28][29] and included 70 men treated with pharmacological (surgical orchiectomy excluded) ADT (with or without prior chemotherapy) for PCa, 52 PCa controls (diagnosed and/or treated with non-ADT therapies currently or previously) and 70 healthy controls (not diagnosed with PCa). Eligible participants were men aged 50-85 years.…”
Section: Participantsmentioning
confidence: 99%
“…This cross-sectional study was conducted parallel to baseline of a randomised controlled trial [27][28][29] and included 70 men treated with pharmacological (surgical orchiectomy excluded) ADT (with or without prior chemotherapy) for PCa, 52 PCa controls (diagnosed and/or treated with non-ADT therapies currently or previously) and 70 healthy controls (not diagnosed with PCa). Eligible participants were men aged 50-85 years.…”
Section: Participantsmentioning
confidence: 99%
“…In fact, both CiC and obesity share several underlying mechanisms that lead to severe skeletal muscle atrophy [ 106 ]. Concurrent gain of WAT and loss of skeletal muscle also occur during ADT [ 107 , 108 ], highlighting not only the importance of maintaining the skeletal muscle quality but also the clinical significance of adiposity, irrespective of CiC.…”
Section: Prostate Cancer and Obesitymentioning
confidence: 99%
“…Studies conducted in PCa patients have shown that ET is an important strategy that can be used to mitigate PCa-related clinical features, such as lower circulating glucose and insulin levels, increased adipose tissue mass, and whole-body inflammatory markers as well as improving hormonal levels [ 15 , 16 , 108 ]. Furthermore, the impact of ET in skeletal muscle was observed by inducing phenotypic alterations mediated by transcriptional responses that occur during and following an exercise session [ 7 ].…”
Section: Exercise Training As An Intervention For Obesity and Prostate Cancermentioning
confidence: 99%
“…Another important consequence of exposure to ADT is sarcopenia, a degenerative loss of muscle mass that is in turn associated with frailty and increased falls risk [69]. When combined with the effects of ADT on BMD, these patients are at an even higher fracture risk with potentially lifethreatening complications [70].…”
Section: Lifestyle Modificationmentioning
confidence: 99%